Challenges and Strategies of Female Leadership in Faith-Based Higher Education Institutions - Indri Indri; Harun Joko Prayitno; Ahmad Muhibbin; Zukhrofa Rizkiana Ramadhani; Ani Syafriati; Dwi Purwati; Wafa Taqiyya; Iswantuti Iswantuti (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
The landscape of women's leadership within Islamic educational institutions, particularly in the Muhammadiyah community, continues to be shaped by complex challenges rooted in prevailing social norms, cultural expectations, and institutional frameworks that often exhibit gender biases. This context frequently hinders the full realization of female leaders' potential and their contributions to organizational development. This qualitative study, focusing on the leadership of female rectors at Muhammadiyah-Aisyiyah Universities (PTMA), aimed to thoroughly investigate the specific obstacles encountered by these women leaders and to delineate the strategic approaches they employ to effectively navigate and overcome such impediments. Employing an empirical qualitative methodology, data were meticulously gathered through in-depth interviews with prominent women leaders in selected PTMA, complemented by a comprehensive analysis of relevant institutional policies and regulatory documents. The research findings reveal that despite the persistent presence of structural and patriarchal barriers, these female leaders adeptly adopt adaptive leadership strategies. These strategies encompass the crucial strengthening of social networks, fostering highly participatory decision-making processes, and driving significant managerial innovation within their respective institutions. Crucially, these insights underscore the profound significance of women's leadership in Islamic higher education, demonstrating their capacity not only to confront adversity but also to instigate transformative changes in institutional management and substantially enhance educational quality. The implications suggest a robust model for leadership development that integrates adaptive and inclusive practices within faith-based educational settings.